P-CARE BPJS ACCEPTANCE MODEL IN PRIMARY HEALTH CENTERS - Hosizah Hosizah (UNEJ e-Proceeding, 2016)
Electronic Medical Record (EMR) is increasingly adopted in the healthcare facilities. The concept of EMR used in primary health centers is p-care BPJS. P-Care BPJS is a web-based patient software provided by BPJS intended for primary health care facilities to provide easy data access to the BPJS server including registration, laboratory, diagnosis, treatment and therapy. Recently, implementation failure of electronic information systems is known caused by not only the quality of technical aspects but also the user’s behavior. It is known as applying the Technology Acceptance Model (TAM). Until now in Indonesia, studies examining the individual acceptance of the use of p-care BPJS have not been done yet. This research aimed to analyze the acceptance model of p-care BPJS in the primary health centers. This study was conducted in five regencies/cities of East Java province, namely Bangkalan, Bondowoso, Lamongan, Malang and Kediri in February-May 2016. The observational research with a quantitative approach with a cross- sectional study design was used to measure the model. A total sample of 30 p-care BPJS users was drawn by multistage random sampling in which of these 30 primary health centers participated. The data collection technique was through using questionnaires to measure the model. Data analysis used both descriptive and inferential statistics. Inferential statistics was performed with Structural Equation Modeling (SEM) by using a SmartPLS 3.0 program consisting of two phases, the measurement model and the structural model. The results of data analysis in the measurement phase indicated that the measurement model was declared fit (good) and met the reliability, convergent validity and discriminant validity. In the phase of structural model, it indicated that p-care BPJS acceptance model in the primary health centers was formed by Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) through Attitude towards use of p-care BPJS and Behavioral Intention to use p-care BPJS. Goodness of Fit (GoF) index of this model was 0.741. It is good or fits the model. The R2 for the model was 0.790. This means that the diversity of behavioral data of p-care BPJS use in primary health centers that can be explained by the construct is 79%, the remaining 21% is explained by other constructs that are not included in the model. The determinant of p-care BPJS acceptance model in the primary health centers is Perceived Ease of Use (PEOU) and Perceived Usefulness (PU). Thus, users of p-care BPJS need to be trained on an ongoing basis to keep up to date in understanding the latest version.